Body mass index trajectories and mortality in community-dwelling older adults: population-based cohort study - Martin C Gulliford; Hari Pai (BMJ Open)
Objective Both low and high body mass index (BMI) have been associated with greater mortality in older adults. This study aimed to evaluate the trajectory of BMI in the final years of life.Methods A population-based cohort study was conducted including community-dwelling adults in the English Longitudinal Study of Ageing between 1998 and 2012. BMI was evaluated in relation to age and years before death. Number of long-term conditions, cigarette smoking and socioeconomic position were evaluated as effect modifiers.Results Data were analysed for 16 924 participants with 31 857 BMI records; mean age at study starts, 61.6 (SD 10.9) years; mean BMI, 27.5 (4.7) Kg/m2. There were 3686 participants (4794 BMI records) who died and 13 238 participants (27 063 BMI records) who were alive at last follow-up. Mean BMI increased with age to 60–69 years but then declined, but the age-related decline was more rapid in decedents. From 4 to 7 years before death or end of study, adjusted mean BMI was 0.87 (95% CI 0.50 to 1.24) Kg/m2 lower for male decedents than survivors and 1.02 (0.56 to 1.47) lower in women; and from 3 to 0 years before death, BMI was 1.39 (0.98 to 1.80) Kg/m2 lower in male decedents and 2.12 (1.60 to 2.64) lower in female decedents. Multiple long-term conditions and lower socioeconomic position were associated with higher peak BMI and greater BMI decline; current smoking was associated with lower BMI and greater BMI decline.Conclusions In community-dwelling older adults, mean BMI enters an accelerating decline from up to 8 years before death. Multiple long-term conditions, smoking and lower socioeconomic position are associated with BMI decline.